Troubling the Water : A Dying Lake and a Vanishing World in Cambodia - Seiff, Abby (Book collections on Project MUSE., 2022)
"Troubling the Water uncovers the threats of the Tonle Sap and what its disappearance means for the survival of those that count on it. But it is much more than that; It is a story that taps into a universal fact we will all have to contend with soon: we are destroying our resources in a way that cannot be undone"--